Effects of Oxygen Plasma Treatment on Fermi‐Level Pinning and Tunneling at the Metal–Semiconductor Interface of WSe2 FETs. (22nd January 2023) - Lee, Kwangro; Ngo, Tien Dat; Lee, Sungwon; Shin, Hoseong; Choi, Min Sup; Hone, James; Yoo, Won Jong
Abstract: Recently, 2D materials have been intensively investigated for their novel nanoelectronic applications; among these materials, tungsten diselenide (WSe2 ) is attracting substantial research interest due to its high mobility, sizable bandgap, and ambipolar characteristics. However, Fermi‐level pinning (FLP) at the metal–semiconductor contact is a critical issue preventing further integration of WSe2 to complementary metal–oxide–semiconductor (CMOS) technology. In this study, a facile doping method of oxygen (O2 ) plasma treatment and an aging effect to overcome the FLP of WSe2 field‐effect transistors (FETs) are utilized. After aging, a reduction is observed in FLP on oxidized WSe2 FETs, along with a decrease in pinning factor ( S ) for holes from −0.06 to −0.36. Further, the field‐effect mobility of high‐ (Pd) and low‐ (In) work‐function contacted WSe2 devices indicates the presence of more improvement in high‐work‐function metal‐contacted p‐type WSe2 FETs, which further strengthens the Fermi level de‐pinning behavior attributed to the O2 plasma and aging processes. The existence of different tunneling behaviors of Pd and In devices also confirms the effect of O2 plasma doping into WSe2 FETs. Ultimately, this work demonstrates a simple and efficient method for achieving the de‐pinning of Fermi‐levels and modulating FLP of 2D FETs. Abstract : Upon aging in vacuum, the p‐type semiconductor property of O2 ‐plasma‐treated 2D WSe2 field‐effect transistors (FETs) is gradually recovered from the metallic property. Furthermore, unwanted Fermi‐level pinning occurring at the metal contact in the pristine WSe2 FETs is greatly reduced, as a result of the recovered semiconducting property of the aged FET devices.